Readiness Factor Identification on Kabupaten Karawang SMEs towards Industry 4.0 Era - Sari, Rianita Puspa; Santoso, Deri Teguh (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2020)
This study aims to explore the readiness of SMEs Karawang in terms of Technology, Organization, Environment (TOE) Framework and technological readiness (TRI) for benefits of industry 4.0 (BOI) in the dimension of industry 4.0 (DOI), viewed from different business scale groups; micro-businesses (group 1) and small-medium businesses (group 2), with a random sampling of 300 SMEs samples using the multigroup-SEM method. The results showed that the feasibility of the research model was quite good from the results of the structural test of the multigroup-SEM. In the micro business (group 1), managerial (TOE) and technology (TRI) MSME readiness factors influence the use of technology pillars in the industry dimension (DOI). In contrast, in small and medium business groups (group 2), the managerial (TOE) and technology (TRI) readiness of MSMEs influence the use of (DOI) and the benefits of the industrial era 4.0 (BOI).